2012
DOI: 10.1038/nnano.2011.240
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretically induced aqueous flow through single-walled carbon nanotube membranes

Abstract: Electrophoresis, the motion of charged species through liquids and pores under an external electric field, has been principle source of chemical pumping for numerous micro- and nano-fluidic devices platforms. Recent studies of ion current through single or few carbon nanotube channels range from near bulk mobility to 2-7 orders of magnitude of enhancement but cannot directly measure ion flux. Membranes, with large number of nanotube pores, allow independent confirmation of ion current and flux. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(144 citation statements)
references
References 38 publications
8
136
0
Order By: Relevance
“…We found that ion mobility also scales inversely with membrane thickness (Extended Data Fig. 7a, b), which may conform to previous observations 25 . We then performed molecular-dynamics simulations of multilayer membranes of MoS 2 to investigate the power generated by those membranes.…”
Section: Letter Researchsupporting
confidence: 92%
“…We found that ion mobility also scales inversely with membrane thickness (Extended Data Fig. 7a, b), which may conform to previous observations 25 . We then performed molecular-dynamics simulations of multilayer membranes of MoS 2 to investigate the power generated by those membranes.…”
Section: Letter Researchsupporting
confidence: 92%
“…However, complex fabrication and the difficulty in obtaining CNTs with subnanometer diameters remain challenges. An alternative approach is to directly deposit CNTs onto a porous membrane and remove salt via capacitive electrostatic interactions [21][22][23] ; however, the salt adsorption capacity is limited 24,25 . Other methods, such as surface functionalization with carboxylic and alkoxysilane-based chemical groups, were also reported to enhance water flux and desalination efficiency of such CNT-based membranes, for example, as demonstrated in the case of membrane distillation 26 .…”
mentioning
confidence: 99%
“…As a result, the computed enhancement in potential barrier for trapping due to ion conductivity gradients at r m of 1 S/m continues to be significant in Figure 3(c) ($8-fold enhancement, with a conservative q c : 0.08 C/m 2 ), even though the EDL is not thick enough to ensure maximum coion exclusion and counter-ion surface conduction within the perm-selective region versus the respective level at r m of 0.2 S/m. However, while electro-osmotic effects on ion migration can be neglected at higher r m (!1 S/m), since electrophoretic ion mobilities are significantly greater than electro-osmotic mobilities in nanochannels [28][29][30] (see supplementary material, S3), this is not the case at r m of 0.2 S/m, where the two mobilities are comparable. 31 The inset (v) of Fig.…”
Section: Conductivity Of the Bulk Media (R M ) Determines The Electrimentioning
confidence: 99%